(untitled) (MMIT Proceedings, 2024)
This article is devoted to the disclosure of the role of flexible forms of labor relations in planning the work environment in companies in Uzbekistan. Taking into account the experience of developed countries, which are actively implementing remote work and flexible working hours, the article examines what advantages can be achieved by developing this area of hiring employees for remote or flexible work.